Potential Publicity of the Remnant Space in the Upper Modern City: London Low-Line Railway Example - Akaydin, Ozlem Eren; Onal, Feride (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2020)
Cities have been exposed to an uncontrolled change, consumption, and transformation process because of the profit-oriented planning systems with the developments dependent on technology and capital. Due to the reasons that can be detailed under major circumstances such as the increase in the private vehicle usage, the planning approaches generated for public spaces during the modernism period, the determination of regional distinctions with stable boundaries, the disconnection in the transitions of public-private spaces, and the inaccurate applications in decontamination of city centres from industry, military and massive transportation areas; caused the existence of the remnant space problematic nature. Especially in cities that are developed very fast, urban outdoor spaces cannot adapt to this process and transform into remnant spaces with generating different problems in daily life. The main theme of the study is to define these problematic urban pieces formally and conceptually in today's upper-modern city context, which is defined with extremism. In the upper-modern city, there are critical changes in public space because of globalization. All the terms and qualifications that are attached to public space; remain incapable because those changes occur in a very fast time period. To explain the upper modern urban space through the scope of anthropology; the urban fabric should produce daily identical interactions, but in upper-modern cities, urban fabric has various losses because of temporary interactions. In the scope of anthropology, the historical and contextual side of the urban space is so valuable, unique, and nominative but in an upper-modern cities, urban space is general and has connectivity problems with its context and close environment. After expanding the meaning of the upper-modern city; remnant space is defined within the interactive relation of the existing similar terms in the international literature. Lands of contempt, empty space, border vacuums, defensible space, lost space, space of uncertainty, awkward space, residual space, gapscape, modern wasteland, and liminal space are associated with the remnant terms. These associated terms helped to explain the remnant space through the emphasis of potentials as new public spaces of the upper-modern cities. The aim of the study is to evaluate the potentials of remnant spaces within the publicity, questioning their spatial offsets in the upper modern city and emphasise the necessity of regenerating these spaces through a theoretical approach that focuses on the human experience. In this context, the Low-Line Railway, which is one of the most important transportation arteries of London, has been examined as a remnant space. The Low-Line refers to the important city flows along the route in between Southwark tube station in the west, London Bridge Station in the east. The most important key approach is to evaluate a remnant space within its unique context to explore its core potential of the remnant space. For this reason, the remnant space is evaluated within its dynamic context by addressing a group of specifications that emphasise the human scale importance as a basis. Resilience; adapting to contextual changes. Placemaking; defining the functional requirements by understanding user needs, regeneration; supporting the remnant space with new values. Social interaction; encouraging active living and recreation. Exemplary; creating an example approach by enhancing biodiversity within the city. Green infrastructure; generating nature-based sustainable solutions for the area. Active pedestrian flow: providing opportunities to reduce the dominance of vehicles. Communication and engagement; getting involved in the user experience, residents, and businesses into the process. Through these criteria, awarded competition projects have been evaluated and potentials of the remnant space have been exposed by enhancing user experience importance.
Keywords: Potential; publicity; remnant space; upper-modern city; Architecture